210Pb in di-calcium phosphate consumed by dairy cows. Issue 5 (3rd September 2018) - da Silva, Cleomacio Miguel; da Silva Filho, Crescêncio Andrade; Neto, João Adauto Souza; de Oliveira Costa Júnior, Carlos Eduardo
Abstract: In the semiarid region of the Brazilian state of Pernambuco, the feedstuffs for dairy cattle contain the mineral supplement of di-calcium phosphate (DCP). This study was carried out to determine the concentration of 210 Pb in samples of di-calcium phosphate (DCP: CaHPO4 ) consumed by dairy cows in Pedra and Venturosa. 210 Pb concentrations ranged from 17 to 256 Bq.kg −1, and although they are below the concentrations reported in Spain (up to 2260 Bq.kg −1 ), they also could be considered to represent a potential risk of chemical toxicity in dairy cows.